Perception of menopause among women of Sarawak, Malaysia - S. A. R. Syed Alwi; I. B. Brohi; I. Awi (BMC, 2021)
Abstract Background Various factors, including menopausal status, educational and social background, culture, and physical and emotional health, may influence women's perceptions of menopause. This study documents the elements influencing attitudes towards menopause among women in Sarawak, Malaysia. Methods A face-to-face interview using a validated questionnaire was conducted with 324 Sarawakian women aged 40-65 to determine the mean age of menopause and perceptions and experiences of menopause among these women. Results The mean age ± standard deviation of the women was 51.37 ± 5.91 years. Ninety (27.8%) participants were premenopausal, 124 (38.5%) perimenopausal and 110 (33.7%) postmenopausal. The majority of these women (228; 70.4%) were local indigenous inhabitants of Sarawak. The findings show that 22.5% of the participants agreed that problems during menopause are a natural process. While 21.9% of the participants suggested that menopause should be treated medically, 32.3% argued that natural approaches for menopause symptoms are better than hormonal treatments. Seventy-five per cent of the women agreed that the absence of menses after menopause is a relief; meanwhile, 61.2% stated that menopause causes unpleasant symptoms. Notably, 51.7% were not sure whether women become less sexually attractive after menopause, and 51.1% were uncertain as to whether they feel less of a woman following menopause. Finally, 81.7% of participants were unsure if sexual activity is more enjoyable after menopause, and 71.9% were uncertain whether changes in life during menopause are more stressful. Among the different menopausal stages, the premenopausal group of women were noted to have more positive perceptions of menopause compared to the peri- and postmenopausal women. The study also observed that women with a better educational background generally had more positive perceptions of menopause. Conclusions The women's perceptions of menopause in this study were found to correspond to those in other studies on Asian women. Women with higher levels of education and premenopausal women comparatively expressed more positive opinions regarding menopause. Lastly, most of the women noted that menopausal symptoms are unpleasant, but that the absence of menses after menopause is a relief.